(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Abylabek Asankanov is one of the famous scholars who have made significant contributions to the development of ethnographic and ethnosociological science in the Kyrgyz Republic. The article discusses the factors that influenced his choice of profession, which defined the career path of the future scientist. It narrates how his close contacts with prominent researchers and experienced mentors during his postgraduate studies at the N.N. Miklukho-Maklay Institute of Ethnography in Moscow broadened his research areas and largely determined the scope of his diverse scientific interests. These interests include not only the problems of socio-cultural development of Kyrgyz villages but also issues related to civic identity and traditional culture. Asankanov was at the forefront of establishing ethnosociological science in Kyrgyzstan, founding his own scientific school. The researcher’s contributions in these areas are revealed based on specific facts. Additionally, it is necessary to emphasize his successes in training mentees and matters related to the organization of scientific work. The article provides a detailed analysis of his main scientific works.